2009
DOI: 10.1007/s10530-009-9640-z
|View full text |Cite
|
Sign up to set email alerts
|

Invasive species and climate change: Conyza canadensis (L.) Cronquist as a tool for assessing the invasibility of natural plant communities along an aridity gradient

Abstract: The predicted reduction in precipitation in the eastern Mediterranean due to climate change may expose the natural plant communities to invasive species. We assessed whether natural plant communities along an aridity gradient in Israel were resistant to invasion by considering differences in abiotic conditions and community characteristics in these regions. We considered Conyza canadensis as a model plant as it is a common invader in the region. We examined the mechanisms and functional traits of both the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…For the Sea of Galilee, the most important water resource in the region, the changes in temperature and wind which effect evaporation along with the changes in rainfall threaten to change the biological makeup of this natural reservoir [ Rimmer et al , 2011; Hambright et al , 1994]. In addition, some natural plant communities may become vulnerable to invasive species because of reduced rainfall [ Har‐Edom and Sternberg , 2010].…”
Section: Resultsmentioning
confidence: 99%
“…For the Sea of Galilee, the most important water resource in the region, the changes in temperature and wind which effect evaporation along with the changes in rainfall threaten to change the biological makeup of this natural reservoir [ Rimmer et al , 2011; Hambright et al , 1994]. In addition, some natural plant communities may become vulnerable to invasive species because of reduced rainfall [ Har‐Edom and Sternberg , 2010].…”
Section: Resultsmentioning
confidence: 99%
“…This can particularly be expected for annual invasive species, which may have an ability to exploit resources earlier, more rapidly or to a greater extent than native perennials (Leffler et al 2011). Consistent with the fluctuating resource theory, a number of studies on invasive annual plants have shown that natural or experimental increase in rainfall facilitated invasion, while drought decreased the success of alien species (Hobbs and Mooney 1991;Dukes and Mooney 1999;Suttle et al 2007;Har-Edom and Sternberg 2010;Suazo et al 2012). Alternatively, alien species with rapid resource acquisition may be favored when drought causes plant mortality in the resident native vegetation, or limits the growth or reproduction of the resident species, which cannot immediately recover when drought stress is alleviated (Jiménez et al 2011;Diez et al 2012;Manea et al 2016).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 87%
“…The vigorous vegetative growth of A. ochroleuca in wadi channels and abandoned fields compared to the drier habitats, such as sandy plains and mountain ranges, could result from enhanced soil water availability and nutrients. In arid and semi-arid regions, soil water availability, especially water pulses in streams, largely determines the growth and productivity of plant communities [ 55 , 56 ], particularly those of invasive herbaceous species [ 57 ]. Plant populations in habitats with low soil moisture availability and nutrients often have low growth rates and small leaves [ 58 ].…”
Section: Discussionmentioning
confidence: 99%